ANALYSIS OF STYLE AND CLASSIFICATION OF ANALYTICAL JOURNALISM - Shukurova Nigora Shavkatovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article presents a brief description of analytical genres of journalism in the English language and investigates various forms related to analytical journalism.